STUDENTS’ POLITENESS PRINCIPLES AND ACADEMIC PERFORMANCE : EVIDENCE FROM HIGHER EDUCATION CONTEXTS - Yessy Prima Putri; Rahmadini Darwas; Yopi Eka Androni (Sekolah Tinggi Bahasa Asing Prayoga Padang, 2026)
Language politeness plays an important role in academic communication because it influences how students interact with lecturers, peers, and the wider academic community. Effective and polite communication may contribute to creating a positive learning environment that supports students’ academic success. This study aims to examine the relationship between students’ politeness principles and their Grade Point Average (GPA) in higher education. The study employed a quantitative correlational design involving undergraduate students from Universitas Metamedia. Data were collected through a politeness questionnaire developed based on Leech’s Politeness Principle, covering the maxims of tact, generosity, approbation, modesty, agreement, and sympathy. Students’ GPA data were obtained from academic records with participants’ consent. The collected data were analyzed using descriptive statistics and Pearson Product-Moment Correlation. The findings are expected to reveal whether language politeness significantly correlates with students’ academic achievement. The study contributes to pragmatic research by highlighting the potential role of politeness in academic communication and student performance. Furthermore, the findings may provide implications for character education and communication ethics in higher education.